2012
DOI: 10.5301/jbm.2012.9140
|View full text |Cite
|
Sign up to set email alerts
|

Murine Double Minute Clone 2 309T/G and 285G/C Promoter Single Nucleotide Polymorphism as a Risk Factor for Breast Cancer: A Polish Experience

Abstract: In a sample of the Polish population, we observed that the MDM2 285C gene variant may be a significant protective factor against breast cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…16,17 This haplotype is widespread across Caucasian populations, but appear to be absent among ethnic Asians and Africans. 24 Previously, we and others have reported that the SNP285C variant may be associated with reduced risk for breast, 16,20 ovarian 16 and endometrial 19 cancer, and others reported a reduced age at cancer diagnosis related to the SNP285G allele among individuals with the Li-Fraumeni syndrome. 41 In contrast, previous reports have indicated SNP285C not to be associated with the risk of either lung 21 or prostate cancer.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…16,17 This haplotype is widespread across Caucasian populations, but appear to be absent among ethnic Asians and Africans. 24 Previously, we and others have reported that the SNP285C variant may be associated with reduced risk for breast, 16,20 ovarian 16 and endometrial 19 cancer, and others reported a reduced age at cancer diagnosis related to the SNP285G allele among individuals with the Li-Fraumeni syndrome. 41 In contrast, previous reports have indicated SNP285C not to be associated with the risk of either lung 21 or prostate cancer.…”
Section: Discussionmentioning
confidence: 96%
“…16,17 The C-allele of SNP285 seems to antagonize the effect of SNP309G by reducing the binding affinity of the Sp1 transcription factor to the MDM2 promoter. 16,18 Moreover, the SNP285C/309G haplotype has been associated with a reduced risk for ovarian, breast and endometrial cancer 16,19,20 but was found not to be associated with risk for cancer of the prostate or lung. 19,21 Finally, the SNP285C has also been found to reduce the risk of BRCA1 related ovarian cancer in individuals carrying the SNP309G allele.…”
mentioning
confidence: 99%
“…Paulin and co-workers found SNP285C in 4.4% of healthy Scottish individuals [19], while Piotrowski and colleagues found the variant C-allele in 10.2 % of healthy Polish individuals [20]. Further, Ryan and colleagues found 6% of Americans of Caucasian ancestry to harbor SNP285C [21], while Renaux-Petel and co-workers found this variant among 5.2% of French individuals diagnosed with germline TP53 mutations [Li-Fraumeni patients; 22].…”
Section: Discussionmentioning
confidence: 99%
“…SNP285 is in complete linkage disequilibrium (LD) with SNP309; thus forming a distinct SNP285C/309G haplotype [ 18 , 19 ]. The SNP285C allele diminish Sp1 binding to the MDM2 promoter, and has been found to be associated with reduced risk for breast, ovarian and endometrial cancer [ 18 , 20 22 ], but was not associated with prostate or lung cancer risk [ 20 , 21 , 23 ].…”
Section: Introductionmentioning
confidence: 99%